Chemical attributes recovery of a degraded soil using pulp manufacture organic compound and planting Mabea fistulifera Mart - Giacomo, Romulo Guimaraes; Alves, Marlene Cristina [UNESP]; Arruda, Otton Garcia de [UNESP]; Souto, Sebastiao Nilce [UNESP]; Pereira, Marcos Gervasio; Teixeira de Moraes, Mario Luiz [UNESP] (Centro Pesquisas Florestais, Ufsm, 2019)
With the production of pulp and paper, industries have daily generated large quantities of solid waste and effluent, constituting a major environmental and economic concern. With the objective of addressing the possibility of using these products in a sustainable way, the aims of this work were to test the effectiveness of an organic compound waste arising from the extraction of cellulose, to consider the recovery of chemical attributes of degraded soil, and to assess the development of Mabea fistulifera Mart. The experiment was installed in an area of the Single Island Power Plant construction located in Selviria-MS in 2010, following randomized complete blocks with split plots, using six treatments: SI-without intervention; D-0-without fertilization; D-AM-mineral fertilizer according to crop need; D-10- composted manure according to crop need; and D-15 and D-20-15 Mg ha(-1) and 20 Mg ha(-1) of the compound, respectively. The soil's chemical properties were studied 12 months after planting in four layers (at 0.00-0.05, 0.05-0.10, 0.10-0.20, and 0.20-0.40 m), along with the development of species, and at three-monthly intervals for a period of 15 months. The results were analyzed by performing analysis of variance, Scott-Knott test for comparison of means, and regression between the different doses of compound at five percent significance level. We conclude that a dose of 20 Mg ha(-1 )was more effective in improving the chemical quality of the soil in the 0.20 m layer. However, we observed a sharp increase in pH in the D-20 treatment in the 0.0-0.05 and 0.05-0.10 m layers, which can have negative influence on the development of tree species.
Keywords: Pulp extraction waste; Degraded area; Soil quality